Adaptation and resilience. Issue 1 (December 2016) - Ebi, Kristie
Abstract Lessons learned, opportunities, and barriers to scaling up health adaptation were identified from evaluation reports and other materials from three multinational health adaptation projects covering 14 low- and middle-income countries and from qualitative data collected through a focus group consultation and interviews with key informants purposively selected for their expertise and role in health adaptation. The national projects aimed to increase resilience to climate-sensitive health outcomes by focusing on incremental improvements in policies and programs to address climate variability and by beginning to establish enabling environments for further adaptation. At this early stage in implementing health adaptation, projects have made limited plans for scaling up specific health adaptation activities outside of normal ministry approaches. Scaling up is needed to prepare for the challenges ahead, including by improving integrated surveillance and other programs to manage the health risks of a changing climate.